The return of Spain to Latin America, reconquest or community of interests? - Casas, Ángel (2016)
This article describes the growing trends in investment and trade bet-ween Latin America and Spain, over the last decade. The author asks if this trend signifies a new type of Spanish conquest; a conquest that takes a financial and commercial form, and occurs in the context of globalization. Finally, the article analyzes the opportunities of establishing a more cooperative relationship between Spain and Latin America, based upon their growing economic exchanges.